INVESTIGATED CHARACTERISTICS OF WEAVING SECTIONS FROM FIELD DATA AND DEVELOPED SIMULATION MODEL - AL-JAMEEL, HAMID ATHAB (Journal of Duhok University, 2017)
Weaving sections widely spread among other traffic facilities. Different types of weaving section have been recognized through various editions of Highway Capacity Manual (HCM). However, the HCM has suffered from inability to represent driver behaviour at these sections.  Therefore, for each type, there is a specific behaviour. This study has focused on investigating weaving characteristics using more than 60 hours of field data and also MIDAS data have involved. The observed characteristics include merging and diverging points for weaving vehicles, how drivers react to weaving sections in terms of changing their speed, cooperative and aggressive behaviour of drivers and effective length for each type of weaving sections. Seven different sites have been investigated in the UK through this study. The results of this study indicate that the effective length is equal to full weaving length for weaving length less than 300m and 200m for the weaving length higher than 300m. Moreover, specific limits for merging and diverging points have been investigated through this study. Then, the simulation model has been developed to find out other characteristics from the simulation model such as applying new effective management by changing weaving section from Type A to Type B with significant increase in the capacity of the new section.